How Theory of Planned Behavior And Perceived Risk Affect Online Shopping Behavior - Bangun, Cicilia Sriliasta; Handra, Tessa (APTISI Transactions on Management (ATM), 2021)
This study aims to analyze the affect of attitude, subjective norm, perceived behavioral control, and perceived risk on intention to shop online and its impact on online shopping behavior. The exogen variables on this study are attitude, subjective norm, perceived behavioral control, and perceived risk. While the endogen variables are intention to shop online and behavior to shop online. Data collection was carried out by distributing 100 questionnaires to users of e-commerce as respondents. By using SEM PLS, this result of this study showed that from 5 initial hypotheses were developed; only 2 hypotheses did not affect to shop online’s behavior; there were subjective norm to intention to shop online; and perceived risk to purchase intention